IMPROVEMENT THROUGH PAI LEARNING AT JAMBI MEDAN PRIVATE SCHOOL - Marlina, Ade; Lubis, Lahmuddin; Arifin, Zainil (Universitas Dharmawangsa, 2024)
This research aims to: (1) determine the morals of Jambi Medan Private Middle School students; (2) To find out how guidance is provided by teachers in handling student morals through PAI learning at Jambi Medan Private Middle School; (3) To determine the factors supporting the moral development of students at Jambi Medan Private Middle School; (4) To find out the obstacles that occur in moral development at Jambi Medan Private Middle School. This thesis was prepared based on field data using a qualitative approach. Data was collected using observation, interviews, documentation. Researchers use qualitative descriptive analysis techniques, namely in the form of descriptions of data instead of numbers that are collected thoroughly from actual field data results. The research results show that: (1) the morals of students at Jambi Private Middle Schools are good (a) students obey school regulations; (b) students performing sunnah prayers; (c) students behave politely towards teachers and friends. (2) How to carry out coaching: (a) provide advice and input to students; (b) carry out the obligations commanded by Allah, and the orders of parents; (c) giving light punishments to students who violate school rules, for example being late. (3) supporting factors for moral development: (a) providing tausyiah to students; (b) shaking hands to create a sense of solidarity between teachers and students; (c) calling parents to help monitor students' behavior at home. (4) knowing what obstacles occur in developing students' morals: (a) students obey the teacher's words, (b) in the school environment students guard themselves so as not to commit immoral acts, (c) every student is aware of the mistakes they have made.